Kebijakan Sekolah dan Strategi Guru Pendidikan Agama Islam dalam Mengatasi Bullying Dalam Membangun Kesadaran dan Empati Siswa MAN 6 JAKARTA Kampus B Cibubur - Al Bani Ridho Pratama; Anggi Kurniawan; Ika Sakiya; Muhammad Zaidan Kaisan (CV Putra Publisher, 2025)
Bullying is a serious problem in the school environment that can have a negative impact on students' mental health and social development. Various efforts are made to prevent this behavior, one of which is by building student awareness through teacher role strategies and school policies. Teachers, especially in the context of Islamic religious education, have a great responsibility in shaping students' character and social behavior through religious values. This study aims to examine the effectiveness of strategies and policies implemented by teachers and schools in building student awareness of bullying and reducing bullying behavior in schools. This study uses a mix methods method with qualitative data obtained through interviews and observations, and quantitative data collected through questionnaires to students. The primary data source is Islamic Religious Education teachers. The results of the study showed that teacher strategies and school policies include socialization about bullying, counseling, religious activities and anti-bullying declarations, significantly increasing students' understanding of the negative impacts of bullying. The data also shows a decrease in bullying cases in schools along with the implementation of these strategies and policies. From this study, Islamic religious education strategies and school policies that are implemented consistently and are effective in building student awareness of bullying and reducing bullying behavior in schools, make the learning environment safer, more harmonious and holistic.